A low humidity sensitivity and ultra-low friction carbon-based composite coating for rubber surface and preparation method thereof
By depositing carbon film on the surface of the rubber seal and spraying a fluorine or chlorine-modified MXene two-dimensional material coating to form an ultra-low friction carbon-based composite coating, the problems of high friction and humidity sensitivity of the rubber seal are solved, and low friction characteristics and stability in a transhumidity environment are achieved.
Patent Information
- Application Number
- CN202310688521.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The rubber seal has a high friction coefficient when the rubber and metal are matched with each other, resulting in friction heat generation, and the rubber seal softens and wears rapidly, resulting in seal failure. At the same time, carbon films are sensitive to humidity, and the friction coefficient varies greatly under different humidity, making it difficult to maintain low friction characteristics in a transhumidity environment.
Magneto-controlled sputtering technology is used to deposit carbon films on the surface of the rubber substrate, and spray the fluorine or chlorine-modified MXene two-dimensional material coating on the surface of the carbon film. After room temperature curing, an ultra-low friction carbon-based composite coating is formed.
The friction coefficient on the rubber surface is significantly reduced to ≤0.10, and remains stable within the humidity range of 10~90%RH, overcoming the problems of high friction and humidity sensitivity of carbon films, ensuring the low friction characteristics and stability of rubber seals in a transhumidity environment.
Smart Images

Figure CN116651714B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a low humidity sensitivity ultra-low friction carbon-based composite coating on a rubber surface and a preparation method thereof, and in particular to an ultra-low friction composite coating of a carbon film / fluorine or chlorine modified MXene two-dimensional material room temperature curing layer on a rubber surface, which is used for preparing dynamic and static seals in a cross-humidity sealing environment, and belongs to the field of solid lubricating materials and tribology. Background Art
[0002] Seal failure is one of the key common technical problems of mechanical equipment sealing systems. When rubber and metal are matched, the friction coefficient is extremely high (µ>1). The friction heat generated by high friction can easily cause the rubber seal to soften and quickly wear out and fail, causing the high-pressure sealing medium to leak from the damaged part and fail to seal, affecting the safe and reliable service of the equipment. Therefore, solving the problem of rubber seal wear failure must start with reducing friction.
[0003] Carbon film has excellent properties such as low adhesion to steel, low deposition temperature (deposition temperature ≤ 100°C, which will not cause fatal damage to the nitrile rubber matrix), controllable composition and mechanical strength, variable structure (such as multi-micro-nano structure, multi-element doping, etc.), and low friction and wear. Therefore, it is an ideal coating for achieving low friction on the rubber surface. Although carbon film can effectively reduce the friction of rubber, it is difficult to further reduce its friction coefficient (the friction coefficient with steel is still ≥ 0.15) by relying solely on carbon film, and it is difficult to fundamentally solve the wear failure problem of rubber sealing materials. Moreover, hydrogen-containing carbon film is extremely sensitive to humidity, and the friction coefficient of the film shows great differences under different humidity. Therefore, how to simultaneously reduce the friction coefficient of the film and increase its humidity insensitivity is the key to expanding the service of rubber dynamic and static seals across humidity environments. Summary of the invention
[0004] The purpose of the present invention is to address the defects of the carbon film on the surface of the current dynamic and static rubber seals that have a high friction coefficient and are seriously dependent on the humidity of the sealing environment. From the perspective of simultaneously reducing the film friction coefficient and improving its humidity insensitivity, a carbon-based composite coating and a preparation method thereof are provided that can achieve low humidity sensitivity and ultra-low friction characteristics on the rubber surface.
[0005] 1. Low humidity sensitivity and ultra-low friction composite coating on rubber surface and preparation method thereof
[0006] The low humidity sensitivity and ultra-low friction carbon-based composite coating on the rubber surface of the present invention and the preparation method thereof are as follows: a carbon film is deposited on the surface of the rubber substrate by magnetron sputtering technology, and then a fluorine- or chlorine-modified MXene two-dimensional material coating is prepared by spraying the surface of the carbon film by a spraying method, and finally cured at room temperature.
[0007] The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, EPDM rubber and silicone rubber, and its surface roughness is ≤100nm.
[0008] The carbon-based film is a hydrogen-containing aC:H film with a thickness of 300 to 500 nm;
[0009] The method of spraying a fluorine or chlorine modified MXene two-dimensional material coating on the surface of the carbon film by spraying and curing at room temperature comprises the following steps:
[0010] ① Plasma cleaning of carbon film surface: plasma bombard the surface of carbon film and cool it to room temperature in a nitrogen environment for standby use;
[0011] ②MXene two-dimensional material modification: MXene two-dimensional material powder is dispersed in fluorine or chlorine modifier, and after a period of time, it is washed, filtered and dried for use;
[0012] ③ Spraying of modified MXene two-dimensional materials: dissolve the fluorine- or chlorine-modified MXene two-dimensional material in an organic solvent, then add epoxy resin monomer and curing agent in proportion, stir and mix evenly, then load into a spray gun and spray it onto the surface of the carbon film, and finally cure it at room temperature.
[0013] In the step ①, the plasma source for the carbon film bombardment treatment is one or more of argon, nitrogen and hydrogen. The bombardment bias voltage is ≥700V, and the bombardment time is 5 to 10 minutes;
[0014] In step ②, the MXene two-dimensional material is one or more of titanium-based, vanadium-based and molybdenum-based. The fluorine modifier is one of FOTS (1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane) and xenon difluoride (XeF2). The chlorine modifier is one of CPTMS ((3-chloropropyl)trimethoxysilane) and xenon dichloride (XeCl2);
[0015] In step ③, the epoxy resin monomer is one or more of bisphenol A, bisphenol F, polyphenol glycidyl ether, aliphatic glycidyl ether and glycidyl ester epoxy resin monomers; the room temperature curing agent is at least one of aliphatic polyamine curing agents, preferably one or more of ethylenediamine, diethylenetriamine, triethylenetetramine and polyethylenepolyamine; the organic solvent is one or more of methanol, ethanol, isopropanol and n-butanol;
[0016] In step ③, the mass ratio of the epoxy resin monomer to the curing agent is 1-5:5-1, and the mass ratio of the total mass of the fluorine- or chlorine-modified MXene two-dimensional material, the epoxy resin monomer and the curing agent to the solvent is 1:1-10;
[0017] The spraying method in step ③ is one of air spraying, airless spraying and HVLP spraying; the spraying distance is 15-30 cm, and the spraying pressure is 0.5-1 MPa;
[0018] In step ③, the room temperature curing time is 2-7 days, and the thickness of the room temperature curing layer is 60-100 nm.
[0019] Figure 1 The schematic diagram of the structure of the ultra-low friction carbon-based composite coating with low humidity sensitivity on the rubber surface of the present invention. The outermost layer of the ultra-low friction composite coating with low humidity sensitivity on the rubber surface designed by the present invention is a MXene two-dimensional material layer, which is easily sheared during the friction process to achieve the ultra-low friction characteristics of the coating. At the same time, the MXene two-dimensional material shows low sensitivity to environmental humidity after being modified by fluorine or chlorine, thereby overcoming the difficult problems of high friction and high sensitivity to humidity of the carbon film on the rubber surface. In addition, the carbon film in the composite coating serves as a bearing layer and a wear-resistant layer, while the surface solidified layer is similar to a modified MXene two-dimensional material solid solution, which can continuously provide a modified MXene two-dimensional material lubricating phase to the friction interface, avoiding the sliding or rolling loss of the two-dimensional material caused by simple coating, and ensuring the stability and durability of the ultra-low friction characteristics with low humidity sensitivity.
[0020] 2. Tribological properties of low moisture sensitivity carbon-based composite coatings on rubber surfaces
[0021] The tribological performance of the low humidity sensitivity ultra-low friction carbon-based composite coating of the present invention was evaluated by a friction and wear tester. The specific friction conditions are: ball-disc rotation mode, normal load 1~5N, friction pair is φ6mm GCr15 steel ball, and the test conditions are an atmospheric environment with a humidity range of 10~90%RH. The test results show that the friction coefficient of the carbon film on the rubber surface is still high (≥0.15), while the friction coefficient of the ultra-low friction carbon-based composite coating of the present invention is significantly reduced (≤0.10), and it is not dependent on the ambient humidity.
[0022] In summary, the present invention deposits a carbon film on the surface of a rubber substrate by magnetron sputtering technology, and then sprays a fluorine or chlorine modified MXene two-dimensional material coating on the surface of the carbon film by spraying, and finally solidifies it at room temperature. The outermost layer of the obtained low humidity sensitivity ultra-low friction carbon-based composite coating is a MXene two-dimensional material layer, which is easy to shear during the friction process to achieve the ultra-low friction characteristics of the coating. At the same time, the MXene two-dimensional material shows low sensitivity to environmental humidity after being modified by fluorine or chlorine, thereby overcoming the high friction and high sensitivity of the carbon film on the rubber surface to humidity. In addition, the carbon film in the composite coating serves as a bearing layer and a wear-resistant layer, and the surface solidified layer is similar to a modified MXene two-dimensional material solid solution, which can continuously provide a modified MXene two-dimensional material lubricating phase for the friction interface, avoiding the sliding or rolling loss of the two-dimensional material caused by simple coating, and ensuring the stability and durability of the low humidity sensitivity ultra-low friction characteristics. The present invention not only overcomes the limitation that the soft surface of the rubber is difficult to achieve ultra-low friction by relying solely on a hard carbon-based film, but also breaks through the bottleneck of the humidity sensitivity of the carbon film. In addition, the specific operation process of the present invention is simple and efficient, can be applied to dynamic and static seals of rubbers with different humidity, and is easy to realize large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of the low moisture sensitivity and ultra-low friction carbon-based composite coating on the rubber surface of the present invention.
[0024] Figure 2 It is a friction coefficient diagram of the unmodified rubber / carbon film surface and the fluorine / chlorine modified composite coating of the present invention. DETAILED DESCRIPTION
[0025] The preparation method and friction performance of the low moisture sensitivity ultra-low friction carbon-based composite coating on the rubber surface of the present invention are further described below through specific examples.
[0026] Example 1
[0027] (1) Cut a 300×300×2 mm black nitrile rubber sheet (surface finish Ra<100 nm) into 20×20 mm 2 The rubber sheet was soaked in a 60℃ soap solution for ultrasonic cleaning for 30 minutes to remove the grease and dirt on the rubber surface; then it was taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 30 minutes to remove the possible residual soap solution; finally, it was blown dry with dry nitrogen and placed in a drying oven at 100℃ for another 20 minutes to evaporate the residual moisture on the rubber surface. The above process was repeated 5 times;
[0028] (2) After the rubber has cooled to room temperature, place it in a magnetron sputtering vacuum chamber. Close the vacuum chamber door and pump the vacuum to ≤1.0×10 –3Pa. 200sccm nitrogen was introduced into the vacuum chamber, and the pressure in the chamber was 4Pa. The high-power pulse bias power supply was turned on, and the rubber was bombarded with nitrogen plasma, with a bias of -700V, a duty cycle of 55%, a frequency of 60KHz, and a treatment time of 35min. The nitrogen was then evacuated, and 300sccm argon was introduced, and the pulse bias was adjusted to -1200V. Other conditions remained unchanged and the bombardment cleaning was continued for 25min.
[0029] (3) After the bombardment, the argon flow rate was adjusted to 45 sccm, the graphite target sputtering power supply was turned on, the target-substrate distance was adjusted to 10 cm, the target current was 3 A, the Ar / CH4 flow ratio was 1.5:1, the substrate bias was -700 V, the gas pressure was 1.0 Pa, the duty cycle was 40%, the frequency was 60 kHz, and the aC:H film deposition time was 90 min;
[0030] (4) After the deposition of aC:H film, turn off the sputtering power supply, turn off the CH4 gas, adjust the bias power supply voltage to -1200V, and adjust the argon gas flow rate to 100sccm to bombard the surface of the carbon film for 10 minutes. After the treatment, turn off the bias power supply, introduce nitrogen, wait for the temperature in the vacuum chamber to cool to room temperature, and then take out the sample for use;
[0031] (5) Disperse an appropriate amount of Ti3C2 powder in FOTS for 24 hours, then wash with deionized water and ethanol by vacuum filtration to remove unbound silane molecules. Finally, add ethanol to the top of the suspension and vacuum dry it at 50°C for later use;
[0032] (6) Weigh 20 mg of fluorine-modified Ti3C2 two-dimensional material powder, add it to about 100 ml of ethanol solution and mix it evenly to obtain solution A, then weigh 10 mg of bisphenol A epoxy resin monomer and 30 mg of ethylenediamine curing agent, add them to solution A and stir evenly to obtain solution B;
[0033] (7) The uniformly dispersed B solution is loaded into an air sprayer, and the spraying distance is adjusted to 15 cm, and the spraying pressure is adjusted to 0.5 MPa to spray the fluorine-modified Ti3C2MXene coating on the surface of the carbon film for 90 seconds; after the spraying, the ultra-low friction carbon-based composite coating sample of the present invention is obtained by drying at room temperature for 2 days. The friction coefficient of the carbon-based composite coating sample is as low as 0.05, and it is basically unchanged in a humidity environment of 10-90% RH.
[0034] Example 2
[0035] (1) to (4) are the same as in Example 1;
[0036] (5) Disperse an appropriate amount of Ti3C2 powder in CPTMS for 24 hours, then wash with deionized water and ethanol by vacuum filtration to remove unbound silane molecules. Finally, add ethanol to the top of the suspension and vacuum dry it at 50°C for later use;
[0037] (6) Weigh 20 mg of chlorine-modified Ti3C2 two-dimensional material powder and add it to about 160 ml of ethanol solution and mix well to obtain solution A. Then weigh 30 mg of bisphenol F epoxy resin monomer and 30 mg of triethylenetetramine curing agent and add them to solution A and stir well to obtain solution B.
[0038] (7) The uniformly dispersed B solution is loaded into an air sprayer, and the spraying distance is adjusted to 15 cm, and the spraying pressure is adjusted to 0.5 MPa to spray the chlorine-modified Ti3C2MXene coating on the surface of the carbon film for 60 seconds; after the spraying, the ultra-low friction carbon-based composite coating sample of the present invention is obtained by drying at room temperature for 7 days. The friction coefficient of the carbon-based composite coating sample is as low as 0.04, and it is basically unchanged in a humidity environment of 10-90% RH.
[0039] Example 3
[0040] (1) Using silicone rubber (silicone rubber surface finish Ra <100 nm), the pre-cleaning step is the same as in Example 1;
[0041] (2) Same as Example 1;
[0042] (3) After the bombardment, the argon flow rate was adjusted to 45 sccm, the graphite target sputtering power supply was turned on, the target-substrate distance was adjusted to 10 cm, the target current was 3 A, the Ar / CH4 flow ratio was 1.5:1, the substrate bias was -700 V, the gas pressure was 1.0 Pa, the duty cycle was 40%, the frequency was 60 kHz, and the aC:H film deposition time was 90 min;
[0043] (4) After the deposition of aC:H film, turn off the sputtering power supply, turn off the CH4 gas, adjust the bias power supply voltage to -1200V, and adjust the argon gas flow rate to 100sccm to bombard the surface of the carbon film for 10 minutes. After the treatment, turn off the bias power supply, introduce nitrogen, wait for the temperature in the vacuum chamber to cool to room temperature, and then take out the sample for use;
[0044] (5) Disperse an appropriate amount of V2C powder in CPTMS for 24 hours, then wash with deionized water and ethanol by vacuum filtration to remove unbound silane molecules. Finally, add ethanol to the top of the suspension and vacuum dry it at 50°C for later use;
[0045] (6) Weigh 10 mg of chlorine-modified V2C two-dimensional material powder, add it to about 300 ml of ethanol solution and mix it evenly to obtain solution A, then weigh 30 mg of bisphenol A epoxy resin monomer and 20 mg of diethylenetriamine curing agent, add them to solution A and stir them evenly to obtain solution B;
[0046] (7) The uniformly dispersed B solution is loaded into an airless sprayer, and the spraying distance is adjusted to 20 cm, and the spraying pressure is adjusted to 1 MPa to spray the chlorine-modified V2C MXene coating on the surface of the carbon film for 30 seconds; after the spraying is completed, the ultra-low friction carbon-based composite coating sample of the present invention is obtained by drying at room temperature for 7 days. The friction coefficient of the carbon-based composite coating sample is as low as 0.04, and it is basically unchanged in a humidity environment of 10-90% RH.
[0047] Example 4
[0048] (1) to (4) are the same as in Example 3;
[0049] (5) Disperse an appropriate amount of Mo2C powder in XeF2 for 24 hours, then wash with deionized water and ethanol by vacuum filtration to remove unbound silane molecules. Finally, add ethanol to the top of the suspension and vacuum dry it at 50°C for later use;
[0050] (6) Weigh 30 mg of fluorine-modified Mo2C2D material powder and add it to about 240 ml of ethanol solution and mix well to obtain solution A. Then weigh 20 mg of aliphatic glycidyl ether epoxy resin monomer and 30 mg of polyethylene polyamine curing agent and add them to solution A and stir well to obtain solution B.
[0051] (7) The uniformly dispersed B solution was loaded into the HVLP sprayer, and the spraying distance was adjusted to 30 cm, and the spraying pressure was adjusted to 1 MPa to spray the fluorine-modified Mo2C MXene coating on the surface of the carbon film for 40 seconds; after the spraying, the ultra-low friction carbon-based composite coating sample of the present invention was obtained by drying at room temperature for 2 days. The friction coefficient of the carbon-based composite coating sample was as low as 0.07, and it remained basically unchanged in a humidity environment of 10-90% RH.
Claims
1. A low humidity sensitivity and ultra-low friction carbon-based composite coating on a rubber surface, which is prepared by depositing a carbon film on the surface of a rubber substrate by magnetron sputtering technology, and then spraying a fluorine or chlorine modified MXene two-dimensional material coating on the surface of the carbon film by spraying, and finally curing at room temperature; The steps of spraying a fluorine or chlorine modified MXene two-dimensional material coating on the surface of the carbon film by spraying and curing at room temperature are as follows: ① Plasma cleaning of carbon film surface: plasma bombard the surface of carbon film and cool it to room temperature in a nitrogen environment for standby use; ②MXene two-dimensional material modification: Disperse MXene two-dimensional material powder in fluorine or chlorine modifier, wash, filter and dry after 20-24 hours for later use; ③ Spraying of modified MXene two-dimensional materials: dissolve the fluorine- or chlorine-modified MXene two-dimensional material in an organic solvent, then add epoxy resin monomer and curing agent in proportion, stir and mix evenly, then load into a spray gun and spray it onto the surface of the carbon film, and finally cure it at room temperature.
2. A low moisture sensitivity ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, EPDM rubber and silicone rubber, and its surface roughness is ≤100nm.
3. The low moisture sensitivity and ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: The carbon film is a hydrogen-containing aC:H film.
4. The low moisture sensitivity ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: In step ①, the plasma source for the carbon film bombardment treatment is one or more of argon, nitrogen and hydrogen; the plasma bombardment bias voltage is ≥700V, and the bombardment time is 5 to 10 minutes.
5. The low moisture sensitivity and ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: In step ②, the MXene two-dimensional material is one or more of titanium-based, vanadium-based and molybdenum-based; the fluorine modifier is one of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and xenon difluoride; the chlorine modifier is one of (3-chloropropyl)trimethoxysilane and xenon dichloride; the mass ratio of the MXene two-dimensional material to the fluorine modifier is 10~30:1~5, and the mass ratio of the MXene two-dimensional material to the chlorine modifier is 10~30:1~5.
6. The low moisture sensitivity and ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: In step ③, the organic solvent is one or more of methanol, ethanol, isopropanol and n-butanol; the epoxy resin monomer is one or more of bisphenol A type, bisphenol F type, polyphenol type glycidyl ether, aliphatic glycidyl ether and glycidyl ester type epoxy resin monomer; the curing agent is one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, polyethylenepolyamine; the mass ratio of the epoxy resin monomer to the curing agent is 1~5:5~1.
7. The low moisture sensitivity and ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: In step ③, the mass ratio of the total mass of the fluorine- or chlorine-modified MXene two-dimensional material, the epoxy resin monomer and the curing agent to the organic solvent is 1:1~10.
8. The low moisture sensitivity and ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: In step ③, the spraying method is one of air spraying, airless spraying and HVLP spraying; the spraying distance is 15~30cm, the spraying pressure is 0.5~1MPa; the room temperature curing time is 2~7 days.
9. The low moisture sensitivity ultra-low friction carbon-based composite coating for rubber surface as claimed in claim 1, characterized in that: The room temperature curing time is 2 to 7 days, and the thickness of the fluorine or chlorine modified MXene two-dimensional material coating after room temperature curing is 60 to 100 nm.
Citation Information
Patent Citations
Method for constructing high-bearing and low-friction rubber surface through in-situ ion co-implantation
CN113201720A
Mxene reinforced silicate adhesive ceramic coating and preparation method therefor
WO2022253100A1